Testing the PPP Using Unit Root Tests with Structural Breaks: Evidence from Politically Unstable Arab Countries (International Journal of Business, Economics and Management, 2016)
This study examines the validity of the Purchasing Power Parity (PPP) in four Arab countries that recently experienced political instability, those being Syria, Egypt, Tunisia, and Bahrain. Using monthly data of the real effective exchange rates (REER) of the countries in question from 1995 to 2014, the study utilizes the ADF test along with unit root tests that account for endogenous structural breaks in the data, this includes the Zivot and Andrews one structural break test and the Lumsdaine and Papell one, two and three structural breaks tests. The findings were in favor of the PPP in Syria, Egypt and Tunisia when the Lumsdaine and Papell three structural breaks test was applied. The findings also confirm the importance of capturing the right number of the breaks in the data as tests that failed to account for structural breaks in the data were more against the PPP. Interestingly, the findings reveal that the political instability did not cause a structural break for Syria and Egypt, which validates the criticism to the Perron test that exogenously defining structural breaks might not be appropriate.